THE EFFECTIVENESS OF COMBATING WATER EROSION WITH THE HELP OF ARTIFICIAL MOLES (Scientific journal of the Fergana State University, 2024)
Soil rotation is an effective way to protect soil from irrigation erosion. This method involves creating depressions in the soil surface that help retain water and reduce the rate of water runoff, thereby avoiding erosion. In addition, moles help conserve moisture, improve soil fertility and plant growth. Thus, the use of soil mowing can be an effective method of protecting soil from irrigation erosion, helping to preserve the soil layer and improve conditions for agricultural production.